Peranan Asian Deveplomant Bank (ADB) Terhadap Pertumbuhan Ekonomi di Indonesia - Melisa Ramadhani; Rini Puji Astuti; Aneira Meilani Putri; Muhammad Aril; Nur Roziq Ramadhani (CV. ITTC INDONESIA, 2024)
This Study aims to examine the contribution of the Asian Development Bank (ADB) in driving economic growth in Indonesia. Bank for Asian Development, is a multilateral financial institution focused on alleviating poverty in the Asia-Pacific region through financing, technical assistance, and policy development. As one of the international banking institutions, ADB plays a strategic role in supporting economic and social development in various countries, including Indonesia. This study discusses the types of support provided by ADB and its impact on Indonesia's economic growth. The methodology used in this study is a literature review, with data obtained from various reliable sources such as scientific journals, books, and official websites of related institutions. The findings indicate that ADB has made a significant contribution to accelerating infrastructure development, supporting economic policy reforms, and strengthening human resource capacity. Furthermore, ADB has played a role in mitigating disaster impacts, enhancing resilience to health crises, and supporting the transition to sustainable energy. With this comprehensive support, ADB has become one of Indonesia's key partners in promoting inclusive economic stability and growth while helping the country address various global and regional challenges.